A CRITICAL REVIEW ON HYPOTHESIS, PATHOPHYSIOLOGY OF SCHIZOPHRENIA, AND ROLE OF VITAMINS IN ITS MANAGEMENT - Jose, Rosmi; N, Venketeswaramurthy; R, Sambath Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
This review describes about the literatures addressing the role of vitamin supplementation in schizophrenia. Evidence is suggesting that vitamin supplementation includes Vitamin A, Vitamin D, Vitamin E, Vitamin B complex, and Vitamin C may be important in treatment. In schizophrenia, patients may have increased level of homocysteine (Hcy), due to the polymorphism in methylenetetrahydrofolate reductase and hypofunction of N-methyl-D-aspartate receptors. The vitamins main effects are reduced the Hcy level and maintain dopamine and serotonin levels. Add-on treatment with high-dose B vitamins including B6, B9, and B12 and also Vitamin D can significantly reduce symptoms of schizophrenia more than standard treatments alone.